Update on the management of adolescent varicocele - Glassberg, Kenneth I (Medicine Reports, 2010)
The management of adolescent varicocele has evolved over the last 30 years. This article briefly reviews some of the current issues regarding the adolescent varicocele, including (a) the progressive nature of the adolescent varicocele, (b) the degree of asymmetry that necessitates surgery, (c) the wide variability in percentage of repairs performed bilaterally in published adolescent series, and (d) the choice of surgical procedure to be performed.